The Role of Islamic Religious Teachers in Shaping the Character of the Younger Generation in Pasangkayu Subdistrict: The Perspective of Maqasid Al-Syari’ah - Latif, Tazkiah; Sastrawaty, Nila; Asni; Andi, Muhammad Akmal; Patimah (Al-Risalah, 2025)
This study aims to examine the role of Islamic religious counselors in shaping the character of the Islamic youth generation in Pasangkayu District based on Maqasid al-Syari'ah. This is a descriptive qualitative study with a normative theological approach. Data was obtained through observation, interviews, and documentation from religious counselors, religious leaders, community leaders, and the youth generation. The results of the study indicate that the character of the young generation in Pasangkayu District has experienced moral decline, evident from the increase in promiscuity, low interest in learning, the use of gadgets for unproductive activities, and a shallow understanding of religion. Islamic religious counselors are instilling Islamic values through counseling in schools and detention centers, supported by a Memorandum of Understanding (MOU) between both parties, and serving as role models (qudwah hasanah) for the younger generation. The Qur'anic approach method, Surah An-Nahl verse 125, namely bil hikmah (wisdom), mau'izhah hasanah (good advice), and mujadalah (dialogue) which is the best. From the perspective of maqasid al-syari’ah, the role of Islamic religious counselors encompasses the protection of five fundamental aspects of life: (1) Religion (hifz al-din), (2) Life (hifz al-nafs), (3) Mind (hifz al-‘aql), (4) Wealth (hifz al-mal), (5) Progeny (hifz al-nasl). The implications of the research emphasize the importance of the joint role of parents, religious leaders, youth leaders, community leaders, and the government in providing a positive space for the younger generation, as well as increasing the capacity and number of religious counselors for sustainable religious guidance.